2022
DOI: 10.3389/fpubh.2022.892422
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Model Analysis of HIV/AIDS Knowledge, Attitude, and Sex Education Among Freshmen in Jiangsu, China

Abstract: BackgroundThe study of acquired immunodeficiency syndrome (AIDS) related knowledge, attitude, and sex education status of Jiangsu freshmen was conducted, which can provide data support directionally for the prevention work of HIV/AIDS among this population.MethodsMale students (4,006) and female students (4,279) were selected from 20 universities or colleges in the Jiangsu province. The knowledge, attitudes, and sex education of freshmen were conducted with an online questionnaire. The log-binomial regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…Regarding the relationship between HIV/AIDS-related knowledge and health education towards HIV/AIDS, college students who receive more comprehensive education on HIV have a stronger understanding of the virus, in line with previous research [6, 30,34,41]. This group of students demonstrates greater caution and resistance to engaging in risky sexual behavior [6, [23][24][25], resulting in lower HIV incidence compared to those with limited HIV knowledge [22,26].…”
Section: Characteristics Of College Students' Hiv/aids-related Knowledgesupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding the relationship between HIV/AIDS-related knowledge and health education towards HIV/AIDS, college students who receive more comprehensive education on HIV have a stronger understanding of the virus, in line with previous research [6, 30,34,41]. This group of students demonstrates greater caution and resistance to engaging in risky sexual behavior [6, [23][24][25], resulting in lower HIV incidence compared to those with limited HIV knowledge [22,26].…”
Section: Characteristics Of College Students' Hiv/aids-related Knowledgesupporting
confidence: 79%
“…Surveys regarding the awareness rate of AIDS-related knowledge in China also showed a large difference among regions ranging from 53.38 to 95.7% [27][28][29]. Compared to Jiangsu Province, which is adjacent to Zhejiang Province, the HIV/AIDS awareness rate among college students in Zhejiang Province is relatively low (87.4% vs. 80.3%) [30]. Additionally, the awareness rate…”
Section: Discussionmentioning
confidence: 99%
“…We found that STUs and PW preferred reagent prices below US$4.35, which may be related to the lack of financial income for STUs and the higher cost of childbirth, resulting in price sensitivity for these two groups. We also observed a higher willingness to self-test among the student population, which may be related to the extensive HIV propaganda work carried out in colleges and universities in the past decade 38 39…”
Section: Discussionmentioning
confidence: 65%
“…Se reportó que los CSR aumentan con la baja educación sexual escolar, resultado que coincide con un estudio realizado en Tanzania, en donde se evaluó el efecto de una intervención educativa sobre comportamientos sexuales seguros en adolescentes (Millanzi et al, 2022), y con un estudio chino en educación sexual sobre el VIH/sida (Tu et al, 2022). También, aumentan los CSR con la baja educación sexual sanitaria, hallazgo consistente con los resultados de estigma anticipado de VIH que reportan un mayor uso de recursos de salud del adolescente cuando está presente (Miller et al, 2018).…”
Section: Discussionunclassified